Leopoldo Laguinge : Casa unifamiliare (2003)
Vivienda unifamiliar en el paisaje natural, Córdoba, Argentina, 1998.
Keywords: VIVIENDAS UNIFAMILIARES; VIVIENDAS DE PERIMETRO LIBRE; ARGENTINA; CORDOBA; LAGUINGE, LEOPOLDO